Becoming evil - Waller, James (Oxford University Press, 2002)
Political or social groups wanting to commit mass murder on the basis of racial, ethnic or religious differences are never hindered by a lack of willing executioners. In Becoming Evil, social psychologist James Waller uncovers the internal and external factors that can lead ordinary people to commit extraordinary acts of evil